2011
DOI: 10.1111/j.1365-313x.2011.04497.x
|View full text |Cite
|
Sign up to set email alerts
|

Building bridges: formin1 of Arabidopsis forms a connection between the cell wall and the actin cytoskeleton

Abstract: SUMMARYActin microfilament (MF) organization and remodelling is critical to cell function. The formin family of actin binding proteins are involved in nucleating MFs in Arabidopsis thaliana. They all contain formin homology domains in the intracellular, C-terminal half of the protein that interacts with MFs. Formins in class I are usually targeted to the plasma membrane and this is true of Formin1 (AtFH1) of A. thaliana. In this study, we have investigated the extracellular domain of AtFH1 and we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 51 publications
10
117
0
Order By: Relevance
“…Inverted formin-2 (INF2) and formin-like protein 2 (FMNL2, also known as FRL3) are also farnesylated and myristoylated, respectively, which promotes their membrane targeting (Chhabra et al, 2009;Block et al, 2012). Moreover, mDia1 and mDia2, as well as the plant formins AFH1, formin1 and class II formin, directly bind phospholipid membranes (Cheung et al, 2010;Ramalingam et al, 2010;Gorelik et al, 2011;Martinière et al, 2011;van Gisbergen et al, 2012). These observations show that localization and activation of formins depend on their diverse interactions and that localization and activation, in some cases, serve as convergent inputs from multiple signalling pathways.…”
Section: Localization and Activation Of Forminsmentioning
confidence: 99%
“…Inverted formin-2 (INF2) and formin-like protein 2 (FMNL2, also known as FRL3) are also farnesylated and myristoylated, respectively, which promotes their membrane targeting (Chhabra et al, 2009;Block et al, 2012). Moreover, mDia1 and mDia2, as well as the plant formins AFH1, formin1 and class II formin, directly bind phospholipid membranes (Cheung et al, 2010;Ramalingam et al, 2010;Gorelik et al, 2011;Martinière et al, 2011;van Gisbergen et al, 2012). These observations show that localization and activation of formins depend on their diverse interactions and that localization and activation, in some cases, serve as convergent inputs from multiple signalling pathways.…”
Section: Localization and Activation Of Forminsmentioning
confidence: 99%
“…This prediction was verified for Arabidopsis Formin1 (AtFH1), AtFH6, and AtFH5 (Banno and Chua, 2000;Cheung and Wu, 2004;Favery et al, 2004;Ingouff et al, 2005). The subcellular localization of AtFH1 was shown by fluorescent protein fusion to be targeted to the plasma membrane and colocalized with a known plasma membrane protein, aquaporin, plasma membrane intrinsic protein PIP2;1 (Martinière et al, 2011). AtFH6 has been shown to be uniformly distributed throughout the plasma membrane and to generate actin cables that serve as tracks for vesicle trafficking for extensive plasma membrane and cell wall biogenesis (Favery et al, 2004).…”
Section: Discussionmentioning
confidence: 81%
“…Firstly, if the actin bundles observed in plasmolysed cells are involved in supporting the protoplast structure, then they would need to be relatively rigid and static. Secondly, Martinière et al (2011) suggested that the cell wall itself acts as a provider of stable anchor points for the dynamic actin cytoskeleton to remodel around, they used formin1 (AtFH1) as an example of a protein that binds both actin microfilaments and the cell wall and is involved in remodelling of the actin cytoskeleton (Figure 4). …”
Section: Discussionmentioning
confidence: 99%
“…Volocity software [PerkinElmer, Massachusetts, USA] was used to track Golgi body movement as has been described previously (Runions et al, 2006;Sparkes et al, 2008;Martinière et al, 2011;Rocchetti et al, 2014).…”
Section: Tracking Golgi Bodiesmentioning
confidence: 99%
See 1 more Smart Citation